the given expression is,
3x + 1/4 - x + 1 1/2
= 3x - x + 1/4 + 3/2
= 2x + (1+6)/4
= 2x + 7/4
= 2x + 1 3/4
so, the given expressions are equivalents.
2 + 6x
take common 2
2(1 + 3x ) or 2(3x + 1)
so the given expressions are also equivalents.
3(x + 1) - (1 - x)
= 3x + 3 - 1 + x
= 4x +2
so the given expressions are not equivalents.
4(x+1) -x -4
4x + 4 - x - 4 = 3x
so,the given expressions are equivalents.
5.5 + 2.2x + 3.8x -4.1
= 1.4 + 6x
so,the given expressions are equivalents.
so in the all given expression only expression 3 is not equivalents.and all others are equivalents